2023
DOI: 10.3389/fpsyg.2023.1136900
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical exercise on anxiety symptoms of college students: A meta-analysis

Abstract: ObjectiveThis study aimed to evaluate the effect of an exercise intervention on improving and alleviating anxiety symptoms in college students with a meta-analytical approach.MethodsSeveral databases (e.g., PubMed, Embase, and the Cochrane Library) were used to search for randomized controlled trials (in short, RCTs) on interventions for physical exercise or aerobic exercise in college students with anxiety symptoms. Stata software, version 16.0, was applied sequentially for traditional meta-analysis, subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
1
6
1
Order By: Relevance
“…Second, several studies suggest a bene cial role of physical activity in anxiety and report a positive association of physical activity with lower levels of anxiety in various populations [37][38][39], including pregnant women and prenatal anxiety [26]. However, in the present study, the intervention did not have any effects on the BAI scores of any group, as no differences in BAI scores were found between the study groups pre-and post-intervention.…”
contrasting
confidence: 58%
“…Second, several studies suggest a bene cial role of physical activity in anxiety and report a positive association of physical activity with lower levels of anxiety in various populations [37][38][39], including pregnant women and prenatal anxiety [26]. However, in the present study, the intervention did not have any effects on the BAI scores of any group, as no differences in BAI scores were found between the study groups pre-and post-intervention.…”
contrasting
confidence: 58%
“…Currently, the clinical application of Qigong exercise is primarily con ned to outpatient settings for individuals with depression or anxiety. [19][20][21][22][23] Advocates of this exercise assert that it aids in blood pressure and sleep regulation, augments muscle strength, and alleviates anxiety and depression levels in patients with anxiety disorders, major depression, post-traumatic stress disorders, and burn-out syndrome (Abbott&Lavretsky, 2013; Guo et.al.,2018;Oh et. al.,2013).…”
Section: Introductionmentioning
confidence: 99%
“…In inpatients, state anxiety may stem from being in an unfamiliar environment, changes in the daily routine, separation from loved ones, and other environmental factors(Ameel etal.,2019; Kilic,2020;Papoulias et al,2014). Conversely, trait anxiety in inpatients is typically attributed to their underlying psychiatric disorders(Kilic,2020;Papoulias et al,2014).According to existing literature, PMR and Tai Chi signi cantly reduce anxiety levels(Hui et.al.,2006;Lin& Gao;2023;Petruzzello et al,1991). The relevant studies indicated that a one-session 20-minute exercise effectively reduced state anxiety but did not signi cantly impact the trait anxiety(Petruzzello et al,1991;Lin& Gao;2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides pharmaceutical treatment, it has been demonstrated that physical and mental exercise, including yoga, can reduce anxiety levels and improve psychological well-being ( 15 19 ). Yoga offers a popular and promising but underrated approach to reduce anxiety ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%